Alterações dimensionais em pacientes submetidos à expansão rápida da maxila com aparelho do tipo Haas - Grossi, Vanessa Silva; Santos-Pinto, Ary dos [UNESP]; Silva, Thais Cristina da; Silva Filho, Omar Gabriel; Bellard, Sônia; Ozawa, Terumi Okada (My University, 2013)
The maxillary atresia is a alteration in the transverse dimension that can result in a unilateral or bilateral crossbite. For correction of atresia of the upper dental arch appliances with the intent to expand the arch of orthopedic or orthodontic manner are used, obtaining across-compatibility between the dental arches. The purpose of this study was to evaluate the dimensional changes of the maxillary in patients in the mixed dentition with atresia in the upper dental arch, using occlusal radiographs taken before, after rapid maxillary expansion and after removal of the appliance. Methods: the sample consisted of 35 patients who used the appliance type conventional Haas, in the mixed dentition, according to the standard protocol for installation, activation, containment and removal of the appliances rapid maxillary expansion. Results: the results confirm that the suture opening occurs in greater quantities in the anterior (4.3 mm) than posterior to (3.74 mm), representing a triangular opening of 7 degrees on average with the posterior opening 87% of the quantity of anterior opening. The molars region expanded about 5 mm, and the base bone 3.7 mm, representing a 74% bone expansion of the expansion teeth.

A atresia maxilar é uma alteração no sentido transversal, que pode redundar em uma mordida cruzada posterior unilateral ou bilateral. Para correção da atresia do arco dentário superior, são utilizados aparelhos com intenção de expandir o arco de maneira ortopédica ou ortodôntica, obtendo assim uma compatibilidade transversal entre os arcos dentários. O objetivo deste estudo foi avaliar as alterações dimensionais da maxila em pacientes na fase de dentadura mista com atresia do arco superior, utilizando radiografias oclusais tomadas antes, após a expansão rápida da maxila e após a remoção do aparelho. Material e métodos: a amostra consistiu de 35 pacientes que utilizaram o aparelho tipo Haas convencional, na dentadura mista, de acordo com o protocolo padrão de instalação, ativação, contenção e remoção dos aparelhos de expansão rápida da maxila. Resultado: o trabalho confirma que a abertura da sutura ocorre em maior quantidade na região anterior (4,3 mm) do que na posterior (3,74 mm), representando uma abertura triangular de 7º em média com a porção posterior, abrindo 87% da quantidade da abertura anterior. Na região posterior, os molares expandiram por volta de 5 mm, e a base óssea 3,7 mm, representando uma expansão óssea de 74% da expansão dentária.
Evaluation of dimensional changes in patients undergoing rapid maxillary expansion appliance type with Haas
Keywords: Interceptive orthodontics; Malocclusion; Activating appliances; Ortodontia Interceptativa; Expansão rápida da maxila; Aparelho de Haas; Arcos dentários